2015
DOI: 10.1002/2015gl064410
|View full text |Cite
|
Sign up to set email alerts
|

Regional air pollution brightening reverses the greenhouse gases induced warming‐elevation relationship

Abstract: Mountain waters, glaciers, hazards, and biodiversity are vulnerable to the impacts of global warming. Warming is projected to amplify over mountains by global climate models, yet meteorological records do not show a uniform acceleration of warming with elevation. Here we explore warming‐elevation relationships using records from 2660 meteorological stations and determine that the vertical gradient of warming rate varies with location. The warming is faster at higher altitudes in Asia and western North America,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 40 publications
3
25
0
Order By: Relevance
“…In addition, our findings confirm the opposite hypothesis of e.g. Zeng et al (2015) and Philipona (2013), who attributed a negative elevationdependent warming to solar brightening and increased radiative forcing at lower elevations. Even though a direct relationship between the observed warming trends and increasing forest cover at high elevation could not be identified, this study illustrates the potential of afforestation to compensate or amplify elevation-dependent warming trends by changing the biophysical surface properties of the landscape (roughness, albedo).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In addition, our findings confirm the opposite hypothesis of e.g. Zeng et al (2015) and Philipona (2013), who attributed a negative elevationdependent warming to solar brightening and increased radiative forcing at lower elevations. Even though a direct relationship between the observed warming trends and increasing forest cover at high elevation could not be identified, this study illustrates the potential of afforestation to compensate or amplify elevation-dependent warming trends by changing the biophysical surface properties of the landscape (roughness, albedo).…”
Section: Discussionsupporting
confidence: 88%
“…The lack of an unequivocal positive or negative sign in ω definitely requires additional efforts to interpret the apparent contradiction in our results and to understand the causes of the observed negative trends. Both Philipona (2013) and Zeng et al (2015) attributed the occurrence of a negative ω to the increase in solar brightening at low elevations, a phenomenon which is generally attributed to an overall reduction in atmospheric pollution sources. In mountainous areas this reduction took place exclusively in the denser populated valleys.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modelling and observational studies investigating such elevation-dependent air warming trends showed, however, that this pattern is not universal. While modelling studies mostly showed a positive elevationdependent warming (i.e Rangwala et al 2015, Kotlarski 2015, Wang et al 2016, a number of observational studies demonstrated that the recent rate of increase in air temperature measured by weather stations, can be higher at low compared to high elevations in different mountain ranges (Philipona 2013, Kirchner et al 2013, Zeng et al 2015, Tudoroiu et al 2016. Such negative elevation-dependent warming (EDW) was interpreted as a consequence of 'solar brightening' (increasing global radiation) at low elevations.…”
Section: Introductionmentioning
confidence: 99%
“…Such negative elevation-dependent warming (EDW) was interpreted as a consequence of 'solar brightening' (increasing global radiation) at low elevations. This was probably triggered by an improved air quality in the most populated areas of the mountain regions (Philipona 2013, Zeng et al 2015, Tudoroiu et al 2016.…”
Section: Introductionmentioning
confidence: 99%